Türk Sırt Çantalı Gezginlerin Seyahat Tarzlarına Göre Günlük Sürdürülebilir Uygulamalarının Karşılaştırılması - Akkuş, Gülizar; Akkuş, Çetin (Turk Turizm Arastirmalari Dergisi, 2019)
The occurrence of a tourism activity depends on the continuity of tourist attractions. The continuity of these attractions is greatly influenced by the sustainable practices of the individuals participating in tourism. In this research, the everyday sustainability practices of the backpackers who participated in longer-term travels compared to other types of tourists were investigated. A total of 244 Turkish backpackers had been reached through snowball sampling. Data were collected in September-October 2018 via a questionnaire. The data were analyzed by independent samples t test and ANOVA. It was determined that the most frequently used sustainability practices were practices pertaining to economic sustainability. Additionally, it was found that sustainability practices were significantly different based on the travelers' travel period, daily working status, daily average spending amount and sponsor supports.